India's year of computing inexpensively. - Singh, S.
This paper reports how the price of PCs in India has become more affordable in 2005. Among the best sellers are the Nova NetPC from Novatium Solutions Ltd. and the Aamar PC from Xenitis Infotech, which sell for only about 100 to 300 dollars. To further reduce costs and maximize function, several PC makers are steering away from the Windows/Intel world by using Taiwanese processors that uses the Linux operating system.
Keywords: PC; Computer makers; Cost reduction; Hardware architecture; Laptops; Thin clients